How does that work? Developing pedagogical content knowledge from subject knowledge - Hillier, J (Rowman and Littlefield, 2013)
The development of subject knowledge and pedagogical content knowledge has been the focus of much educational research and debate in recent years. Of particular interest is the process by which preservice science teachers develop pedagogical content knowledge from their subject knowledge. In the study presented here, a process of writing narrative explanations of scientific phenomena was developed as part of a preservice teacher education course at a U.K. university. This process revealed the importance of teachers having coherent internal accounts to explain phenomena, which they can then share with students through meaningful discourse and joint action. Developing these coherent internal accounts would appear to be part of the process by which subject knowledge is transformed into pedagogical content knowledge